2021
DOI: 10.1002/adfm.202102902
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reconstruction Engineering with Synergistic Effect of Mixed‐Salt Passivation Treatment toward Efficient and Stable Perovskite Solar Cells

Abstract: Surface passivation treatment is a widely used strategy to resolve trap‐mediated nonradiative recombination toward high‐efficiency metal‐halide perovskite photovoltaics. However, a lack of passivation with mixture treatment has been investigated, as well as an in‐depth understanding of its passivation mechanism. Here, a systematic study on a mixed‐salt passivation strategy of formamidinium bromide (FABr) coupled with different F‐substituted alkyl lengths of ammonium iodide is demonstrated. It is obtained bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 54 publications
0
89
0
Order By: Relevance
“…Recently, mixed-salt strategies have received increasing attention for perovskite surface optimization since the synergistic effects can provide effective regulation of the perovskite surface properties. [164,165] As an example, Suo and co-workers reported the adoption of FABr coupled with different F-substituted alkyl lengths of ammonium iodide on Cs 0.05 MA 0.1 FA 0.85 PbI 2.9 Br 0.1 • 0.05PbI 2 surface, in which the FABr forms an ultrathin FAPbI x Br 3−x surface layer to fine tune the energy alignment while the ammonium iodide passivates the surface defects and grain boundaries, leading to a preferred surface morphology. [165] Surface engineering by suitable additives can also create socalled low-dimensional/three-dimensional (3D) perovskite heterostructures, which have been demonstrated to improve the performance of perovskite devices.…”
Section: Additives Engineering For Ohmic Interfacementioning
confidence: 99%
“…Recently, mixed-salt strategies have received increasing attention for perovskite surface optimization since the synergistic effects can provide effective regulation of the perovskite surface properties. [164,165] As an example, Suo and co-workers reported the adoption of FABr coupled with different F-substituted alkyl lengths of ammonium iodide on Cs 0.05 MA 0.1 FA 0.85 PbI 2.9 Br 0.1 • 0.05PbI 2 surface, in which the FABr forms an ultrathin FAPbI x Br 3−x surface layer to fine tune the energy alignment while the ammonium iodide passivates the surface defects and grain boundaries, leading to a preferred surface morphology. [165] Surface engineering by suitable additives can also create socalled low-dimensional/three-dimensional (3D) perovskite heterostructures, which have been demonstrated to improve the performance of perovskite devices.…”
Section: Additives Engineering For Ohmic Interfacementioning
confidence: 99%
“…[32,33] By plotting J sc and V oc as a function of light intensity, as shown in Figure S15 and Figure 2g, the ideality factors closer to 1.0 re-confirm the above conclusion. [34] Different from previously reported PSCs, this PUtailored device displays a self-recovery behavior under heat stimulus. As shown in Figure 3a, we have summarized the dynamic PCE change percentage (ΔPCE) for the control and 0.10 mg mL À 1 PU tailored PSCs before and after heat treatment, which are stored under air conditions free of encapsulation.…”
mentioning
confidence: 55%
“…However, we notice that the BAI‐treated PSCs outperform the 3FBAI‐treated ones in terms of PCE and stability, which is unusual because the additional fluorine atoms in the 3FBAI are usually considered to more efficiently reduce the interfacial trap states and to enhance the hydrophobicity of perovskite film [28–31] . Some previous works have also indicated that increasing the F atoms in the OAS does not always favor the passivation effect [32, 33] . Hence, the passivation mechanism of OAS for the perovskite film in the presence of excess PbI 2 needs to be deeply understood to explain different performances of the PSCs with BAI and 3FBAI treatments.…”
Section: Resultsmentioning
confidence: 85%